Bahasa Arab Dan Tantangan Zaman: Perubahan, Pergeseran, Dan Strategi Pemertahanan - Wwan Saputra, Joniska; Agustina, Nevy; Erlina; Rafli, Zaenal (Universitas KH. Mukhtar Syafaat, 2025)
Language is the primary medium for conveying ideas, thoughts, and information, and it plays a crucial role in all aspects of human life, including the acquisition of knowledge. Arabic, as a language of communication closely associated with Islam, holds a special position in the lives of Muslims because it is the language of the Qur'an and Hadith. However, in the era of globalization—characterized by the rapid flow of information, the dominance of foreign languages, and technological advancements—the existence of Arabic faces serious challenges. The impact of globalization has led to structural and lexical shifts in the Arabic language, including the incorporation of foreign vocabulary, the growing use of Arabizi, and the declining use of Modern Standard Arabic (al-‘Arabiyyah al-Fu???) in daily communication. This study employs a descriptive qualitative approach through literature review and content analysis to identify forms of change and strategies for preserving the Arabic language in the context of contemporary sociolinguistics. The findings reveal that language change is not only driven by external factors such as the dominance of Western culture and technology, but also by internal challenges such as uncommunicative teaching methods and limited educational resources. Relevant and adaptive preservation strategies—such as the digitalization of learning, revitalization of media, language policy reform, and international collaboration—are key to safeguarding Arabic as a symbol of identity, culture, and the transmission of Islamic values. This research affirms that the preservation of Arabic is not merely a technical matter, but is closely linked to efforts to safeguard cultural heritage and the collective integrity of the Muslim community amid global changes.